Relationship between stress and sleep quality among undergraduate physiotherapy students of India who are engaged in clinical posting: a cross sectional study - Dharmita Yogeshwar; E. N. Vipinnath (International Journal of Research in Medical Sciences, 2023)
Background: Physiotherapy students are exposed to different kinds of stress while pursuing their course and this stress affects their sleep quality. The author in this study investigated the relationship between stress and sleep quality among undergraduate physiotherapy students across India. Methods: A cross sectional study was conducted among 150 undergraduate physiotherapy students studying in different physiotherapy colleges across India, using convenience sampling method. Data was collected with help of an Online Google form™. In order to assess the relationship between stress and sleep quality among students, student stress inventory (SSI) and Pittsburgh sleep quality index (PSQI) outcome measures were used. Results: A high prevalence of stress (99.9%) and poor sleep quality (76.7%) were found among students. To analysis the relationship between stress and sleep, Pearson’s correlation coefficient was used, value of correlation coefficient was 0.613 shows a moderate positive relationship between variables and p value was 0.000 (<0.05) shows highly significant relationship between stress and sleep. Conclusions: The study confirms a strong association between stress and sleep among undergraduate physiotherapy students across India. A recommendation for management required promotion of sleep hygiene and including physical activity in the curriculum of students to deal with the stress.